The contribution of scientific research to conservation planning. (July 2018) - Mair, Louise; Mill, Aileen C.; Robertson, Peter A.; Rushton, Steven P.; Shirley, Mark D.F.; Rodriguez, Jon Paul; McGowan, Philip J.K.
Abstract: Conservation planning plays an instrumental role in facilitating progress towards biodiversity targets by providing practitioners with the tools required to allocate resources and implement actions. However, the utility of a burgeoning scientific literature to on-the-ground conservation has been questioned. Given such criticisms, and the lack of progress towards the global Aichi Biodiversity Targets, we aim to assess the contribution of scientific research to the field of conservation planning. We applied topic modelling to a body of literature consisting of 4471 articles pertaining to conservation planning published between 2000 and 2016. We quantified changes in topic popularity, and assessed the extent to which different topics were addressed within the same articles. We found that research into the status of species and habitats was most prevalent, the process of action planning received considerably less attention, and implementation attracted the least research of all. The scientific literature was thus dominated by biological rather than socio-political research, and furthermore showed a general lack of inter-disciplinary research, which is problematic given that ultimately it is the socio-political context that will determine the success of conservation efforts. The number of publications on implementation and monitoring declined over time, suggesting a waning interest in publishing evidence of plan effectiveness, and that limited efforts have been made to address the "implementation crisis". We suggest that filling research gaps, through integration of the social sciences and placing greater value on evidence syntheses, would push scientific research towards greater applicability and help to provide the necessary information to achieve global biodiversity targets.